Bond-slip effect in the assessment of RC structures subjected to seismic actions - Lobo, Paulo Silva (2015)
The effect of bond-slip in the assessment of reinforced concrete structures under static or dynamic cyclic loads with numerical models may be significant. Its relevance is discussed in this paper, by analysis of the correlation of experimental and analytical results. The latter were obtained with a perfect bond-based model and with a fiber-section beam-column model which makes it possible to consider the effect of bond-slip in the vicinity of exterior as well of interior joints of reinforced concrete frame structures. The experimental results consist of a shaking table test of a reinforced concrete frame, with predominant flexural condition, in agreement with the premisses of this research. The model with bond-slip was capable of predicting the structural behaviour in a very satisfactory manner. Furthermore, the results of the assessment including bond-slip are significantly more accurate than those assuming perfect bond.